INVESTIGATION OF THE COMMERCIAL SITUATION AMONG BEEKEEPERS IN HUNGARY FROM 2010 TO THE PRESENT - Margit Csipkés (University of Oradea, 2021)
The beekeeping and beekeeping sectors are very important sectors on a global scale. This is because these sectors play a key role in agriculture and therefore play an essential role in the food supply of humankind. In our research, we would like to examine this global process at the Hungarian level (what commercial opportunities do Hungarian beekeepers have). The main goal of our research is to gain insight into the commercial situation of beekeepers and to help beekeepers who read this research sell their products more efficiently. We chose this topic because in the current COVID period, it is important to implement a healthy diet in our diet (to which honey can contribute). In our research, we also conducted a questionnaire survey (at the national level among Hungarian consumers). The questionnaire was completed by more than 650 people, and the analysis was performed based on the responses received. We also conducted a survey on the part of farmers, in which we analyzed the investment of a real economy in the sector. Based on the conclusions obtained in the analyzes, we compiled the SWOT analysis, in which the advantages, disadvantages, opportunities and dangers of the sector were presented. Our aim is to get a real picture of the commercial situation of beekeepers in Hungary by conducting research, which may also have an impact on honey consumption in Romania.